Individualised antimicrobial dosing in critically ill patients undergoing continuous renal replacement therapy: focus on total drug clearance. Issue 3 (13th January 2017) - Ruiz, Jesus; Favieres, Cassandra; Broch, Maria Jesús; Villarreal, Esther; Gordon, Monica; Quinzá, Adrián; Castellanos Ortega, Álvaro; Ramirez, Paula
Abstract : Background: Continuous renal replacement therapy (CRRT) is common practice in critical care patients with acute renal failure. Objectives: To evaluate the adequacy of antimicrobial doses calculated based on the total drug clearance and dose recommended by different guides in critically ill patients undergoing CRRT. Methods: Retrospective observational study. Patients admitted to a critical care unit during May 2014 to May 2016 and subjected to CRRT were included. The recommended dose was established as the product of the usual dose of the drug by total drug clearance. Results: 177 antimicrobial agents, used in 64 patients were analysed; 45 (25.4%) antimicrobials were given in an insufficient dose (<20%) according to the theoretical calculation. Following the recommendations in the revised guidelines, between 10% and 20% of antimicrobials were given in insufficient doses. A higher success rate of treatment in those patients not receiving a low drug dosage was seen (35.2% vs 24.0%). Conclusions: There is a great disparity between the antimicrobial dose prescribed, recommended and calculated based on drug clearance in critically ill patients undergoing CRRT.